Chondroitin Sulfate- and Decorin-Based Self-Assembling Scaffolds for Cartilage Tissue Engineering. - Lourdes Recha-Sancho; Carlos E Semino (PLoS ONE, 2016)
Cartilage injury and degenerative tissue progression remain poorly understood by the medical community. Therefore, various tissue engineering strategies aim to recover areas of damaged cartilage by using non-traditional approaches. To this end, the use of biomimetic scaffolds for recreating the complex in vivo cartilage microenvironment has become of increasing interest in the field. In the present study, we report the development of two novel biomaterials for cartilage tissue engineering (CTE) with bioactive motifs, aiming to emulate the native cartilage extracellular matrix (ECM). We employed a simple mixture of the self-assembling peptide RAD16-I with either Chondroitin Sulfate (CS) or Decorin molecules, taking advantage of the versatility of RAD16-I. After evaluating the structural stability of the bi-component scaffolds at a physiological pH, we characterized these materials using two different in vitro assessments: re-differentiation of human articular chondrocytes (AC) and induction of human adipose derived stem cells (ADSC) to a chondrogenic commitment. Interestingly, differences in cellular morphology and viability were observed between cell types and culture conditions (control and chondrogenic). In addition, both cell types underwent a chondrogenic commitment under inductive media conditions, and this did not occur under control conditions. Remarkably, the synthesis of important ECM constituents of mature cartilage, such as type II collagen and proteoglycans, was confirmed by gene and protein expression analyses and toluidine blue staining. Furthermore, the viscoelastic behavior of ADSC constructs after 4 weeks of culture was more similar to that of native articular cartilage than to that of AC constructs. Altogether, this comparative study between two cell types demonstrates the versatility of our novel biomaterials and suggests a potential 3D culture system suitable for promoting chondrogenic differentiation.